Plain refuge - Lynn, Dana R. (Lynn, Dana R. Amish country justice., 2020)
After overhearing an illegal weapons deal, Sophie Larson knows two things: her uncle's a dangerous criminal, and he wants her dead. Now undercover cop Aiden Forster has no choice but to blow his cover and protect Sophie by hiding her and her deaf sister in Amish country.